Comparison Among Manual Facial Approximations Conducted by Two Methodological Approaches of Face Prediction. Issue 5 (23rd February 2017) - Herrera, Lara Maria; Strapasson, Raíssa Ananda Paim; Zanin, Alice Aquino; da Silva, Jorge Vicente Lopes; Melani, Rodolfo Francisco Haltenhoff
Abstract: This study verified the difference between two methods of forensic facial approximation (FFA) regarding recognition and resemblance rates. Three‐dimensional models of skulls were obtained from computerized tomography (CT) scans of two subjects (targets). Two manual FFAs were performed for each target, by applying two different guidelines for the facial structures (what we called "American method" (AM) and "Combined method" (CM)). Unfamiliar assessors evaluated the sculptures by recognition and resemblance tests. The AM was that which allowed more correct responses of recognition and higher resemblance's scores for the male target ( p  < 0.001). Regarding guidelines for modeling characteristics of the face, the ones that are practical and easily performed for sculptures, such as the length of the anterior nasal spine multiplied by 3 for nose prediction, may offer better results in terms of resemblance.